2009
DOI: 10.1007/s00402-009-0961-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pre-emptive analgesia with bupivacaine on acute post-laminectomy pain

Abstract: Our data suggests that pre-emptive analgesia via perineural infiltration of bupivacaine is a simple, and effective method for post-operative acute pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Mordeniz et al evaluated the analgesic effects of a perineural infiltration with 2 ml of bupivacaine 0.5% [39]. Perineural infiltration was defined as the infiltration of local anaesthetics in the irritated neural root sheath, before root extraction.…”
Section: Locoregional Anaesthesiamentioning
confidence: 99%
“…Mordeniz et al evaluated the analgesic effects of a perineural infiltration with 2 ml of bupivacaine 0.5% [39]. Perineural infiltration was defined as the infiltration of local anaesthetics in the irritated neural root sheath, before root extraction.…”
Section: Locoregional Anaesthesiamentioning
confidence: 99%
“…In spine surgery, the deep neural blocks are already applied using neuraxial,[ 30 ] and the neural sheath block which is promising, as 41% of patients required no analgesia till discharge. [ 31 ] However, surgical exposure is required, so it may be suitable for discectomy. Likewise, the epidural and intrathecal administration are effective for analgesia in scoliosis surgery,[ 30 ] but the evidence mostly limits its implication to postoperative analgesia, Practically, there is a high rate of epidural failure.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately most reports described local instillation after incision [54,[91][92][93][94] immediately after exposure of the affected nerve root or the more superficial layers before closure, all of which, despite some authors have suggested [91,92], cannot be considered as 'preemptive' but rather 'preventive'.…”
Section: Peripheral Blocks and Local Infiltration Techniquesmentioning
confidence: 99%